Botryllus flavus Sanamyan & Sanamyan, 2017, n. sp. ... - Sanamyan, Karen; Sanamyan, Nadya (Zenodo, 2017)
Botryllus flavus n. sp. (Figures 6, 7) Botryllus sp. Sanamyan, 2000: 76. Botryllus magnus: Sanamyan & Sanamyan, 2010: 245 (Kamchatka). Not B. magnus Ritter, 1901: 255 (Alaska). Sanamyan, 2000: 76 (Commander Islands). Material examined. Holotype: KBPGI 1449 /1, Kuril Islands, Matua Island, Point Kluv, 17 m, 25.08.2016. Paratypes: KBPGI 1450 /2, Matua Island, Point Kluv, 15 m, 26.08.2016, one colony. Additional material examined. Pacific coast of Kamchatka, Starichkov Island, 28.07.2004, 19 m, one colony (Figures 6 C, D); 21.09.2004, 20 m, one colony; Kuril Islands, Atlasova Island, 17 m, 26.07.1989, one colony. Description. The species forms extensive sheets encrusting stones. The colony of the holotype is 8 x 5 cm in extent and from 5 to 10 mm thick (preserved). The surface is clear, sometimes with some sediment attached on the periphery of the colony or between the systems, but usually free from foreign matter (Figure 6). The common tissue of the colony may be depressed between some systems, or even ... : Published as part of Sanamyan, Karen & Sanamyan, Nadya, 2017, Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific), pp. 301-321 in Zootaxa 4232 (3) on pages 307-310, DOI: 10.11646/zootaxa.4232.3.1, http://zenodo.org/record/293689 ...